Applying Customer Lifetime Value to Major League Baseball Season Tickets - John T. Drea; Lucas Marlow; Lauren K. Mense (Journal of Applied Sports Management, 2017)
Customer lifetime value (CLV) is a commonly used metric for assessing marketing performance among businesses; however, there is little evidence of the use of CLV in Major League Baseball (MLB). The authors provide a methodology for calculating CLV for season ticket buyers to properly account for all direct revenue streams for a fan attending an MLB game, including ticket, concession, parking, and auxiliary revenues. Applications for customer lifetime value for MLB teams includes measuring the effectiveness of marketing activities, identifying seating that is over/under priced, and assisting in the management of fan experiences.
Keywords: Customer lifetime value; major league baseball; metrics; sports marketing; season tickets